Maternal mortality in hilly districts of Nepal - Shrestha, B (Journal of Institute of Medicine Nepal, 2010)
Background: Maternal mortality is a vital indicator and exhibits great disparity between developed and developing countries. The challenging nature of measuring maternal mortality has made it necessary to perform an action-oriented means of gathering information on where, how and why deaths are occurring; what kinds of action are needed and have been taken. A maternal death review is an in-depth investigation of the causes and circumstances surrounding maternal deaths. The objectives of the present study are to describe the socio-cultural and health service factors associated with maternal deaths in rural hill districts of Nepal. Methods: We reviewed 33 maternal deaths of women who tried to reach or reached health care services in three remote districts of Nepal, namely Baglung, Dolakha and Ramechhap. A verbal autopsy technique was applied for 33 of the cases. Individuals who had witnessed any stage during the process leading to death were interviewed. Health care staffs who participated in the provision of care to the deceased were also interviewed. All interviews were tape recorded and analyzed using a grounded theory approach. The standard WHO definition of maternal deaths was used. Results: The socioeconomic background of the cases including caste, ethnicity, geography, direct cause of death, place of death and care givers during delivery were included to analyze each cases. The following items evolved as important: underestimation of the severity of the complication, lack of family support, lack of transportation, prolonged transportation, seeking care at more than one medical facility and delay in receiving prompt, lack of money for transportation and health service, delay in reaching an appropriate medical facility, and lack of appropriate care after reaching the hospital. Conclusion: Women in rural hill area faces variety of problems to access to care for obstetric emergencies, hence maternal mortality is prevalent among poor women. Lack of awareness and family support on safe birth preparedness, danger signs of pregnancy, delivery and post natal period, disorganized health care with lack of referral and support for transport and health service networking prompt response to emergencies with quality care are major factors contributing to a continued high mortality rate. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 7-13